Actinopterygii, siluriformes, loricariidae, loricariichthys platymetopon isbrücker and nijssen, 1979: First record in reservoir of canoas II, middle paranapanema river, border of the states of são paulo and paraná, brazil - Souto, Ana Carolina [UNESP]; Vidotto-Magnoni, Ana Paula [UNESP]; Brandão, Heleno [UNESP]; Ramos, Igor Paiva [UNESP]; Carvalho, Edmir Daniel [UNESP] (Pensoft Publishers, 2011)
First record of the cascudo, Loricariichthys platymetopon Isbrücker and Nijssen, 1979 in Canoas II Reservoir (Middle Paranapanema River, border of the states of São Paulo and Paraná, Brazil). Its occurrence is due to the flooding of Sete Quedas waterfall, as a result of the construction of Itaipu Reservoir. Furthermore, there is absence or low abundance of natural predators, like Salminus brasiliensis, since this species has difficulties to adapt or even survive in reservoirs. © 2011 Check List and Authors.